Analysis of Project-Based Learning Conducted in Bina Nusantara University Bandung - Rozi Iskandar, Isna Fachrur (Universitas Pahlawan Tuanku Tambusai, 2024)
Project-Based Learning (PjBL) is an innovative pedagogical approach that emphasizes student-centered learning through active engagement in real-world projects. In this educational model, students tackle complex problems or challenges, working collaboratively in groups to explore, research, and develop solutions. Bina Nusantara University in Bandung has implemented PjBL as part of its curriculum, integrating it with character building courses under the Character-Building Development Center (CBDC). The program aims to provide students with practical learning experiences aligned with the community's needs while fostering essential skills such as critical thinking, time management, and teamwork. Throughout the PjBL process, students are involved in formulating project proposals, conducting research, implementing projects in the community, and presenting their findings. Challenges encountered by students include time management, group dynamics, and adapting to real-world constraints. However, the experience offers opportunities for personal growth and skill development. The analysis of participants in PjBL at Bina Nusantara Bandung reveals the significance of this educational approach in enhancing students' academic motivations, problem-solving abilities, and sense of ownership in their learning. The collaboration between students and community partners fosters mutual learning and contributes to community development. As PjBL continues to evolve, further research and refinement of this approach are necessary to optimize its effectiveness in preparing students for the challenges of the future.